Painful Hand Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A 14-year-old boy with habitual painful seizures of the backs of both hands since age 4 is reported from the Department of Pediatric Neurology, Osaka Medical Center, Japan.